ANALYSIS OF THE EFFECTIVENESS OF PERFORMANCE ASSESSMENT TOOLS FOR DEVELOPING SCIENCE PROCESS SKILLS IN THE GENERAL NATURAL SCIENCES COURSE - Rina Novianty (Penelitian dan Pengembangan Ilmu, 2025)
This study aims to analyze the effectiveness of performance assessment tools in developing students’ science process skills (SPS) in the General Natural Science course. A total of 97 students from various study programs participated as respondents by completing a Likert-scale questionnaire consisting of 40 items. The findings indicate that the performance assessment tools fall into the effective category, with an average score of 4.154 (83.07%). All measured dimensions, conceptual understanding, learning objectives, thinking skills, contextual factors, and SPS were categorized as effective with a high level of consistency. These results align with the principles of authentic assessment and inquiry-based learning, which emphasize the role of process-oriented assessment in developing students’ scientific competencies. This study contributes theoretically to strengthening the implementation of performance assessment in higher education and provides practical recommendations for lecturers in designing comprehensive assessment strategies.